Predictors and prognosis of delirium among older subjects in cardiac intensive care unit: focus on potentially preventable forms. Issue 7 (1st October 2020) - Mossello, Enrico; Baroncini, Caterina; Pecorella, Laura; Giulietti, Chiara; Chiti, Maurizio; Caldi, Francesca; Cavallini, Maria Chiara; Simoni, David; Baldasseroni, Samuele; Fumagalli, Stefano; Valoti, Paolo; Stroppa, Stefano; et al.
Abstract : Background: Delirium is a common and potentially preventable condition in older individuals admitted to acute and intensive care wards, associated with negative prognostic effects. Its clinical relevance is being increasingly recognised also in cardiology settings. The aim of the present study was to assess the prevalence, incidence, predictors and prognostic role of delirium in older individuals admitted to two cardiology intensive care units. Methods: All patients aged over 65 years consecutively admitted to the two participating cardiology intensive care units were enrolled. Assessment on admission included acute physiological derangement (modified rapid emergency medicine score, REMS), chronic comorbidity, premorbid disability and dementia. The Confusion Assessment Method–Intensive Care Unit was applied daily for delirium detection. Results: Of 497 patients (40% women, mean age 79 years), 18% had delirium over the entire cardiology intensive care unit course, half of whom more than 24 hours after admission (incident delirium). Advanced age, a main diagnosis of ST-segment elevation myocardial infarction or acute respiratory failure, modified REMS, comorbidity and dementia were independent predictors of delirium. Adjusting for patient's features on admission, incident delirium was predicted by invasive procedures (insertion of peripheral arterial catheter, urinary catheter, central venous catheter, naso-gastric tube and intra-aortic balloon pump). In a logistic regression model, delirium was an independent predictor of inhospital mortality (odds ratio 3.18, 95% confidence interval 1.02, 9.93). Conclusions: Eighteen per cent of older cardiology intensive care unit patients had delirium, with half of the cases being incident, thus potentially preventable. Invasive procedures were independently associated with incident delirium. Delirium was an independent predictor of inhospital mortality. Awareness of delirium should be increased in the cardiology intensive care unit setting and prevention studies are warranted.